2019
DOI: 10.3389/fnbeh.2019.00093
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Reverses Depression Model-Induced Alteration of Dendritic Spines in the Brain Areas of Mood Circuit

Abstract: Depression is one of the most prevalent psychiatric disorders. Exercise has been shown to be effective in the amelioration of depression, but the underlying mechanism remains largely unknown. Alterations in the density and morphology of dendritic spines are associated with psychiatric diseases. Chronic unpredictable mild stress (CUMS) is an established animal model of depression. The aim of this study was to determine whether treadmill exercise reverses CUMS-induced both depression-like behaviors and alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
(85 reference statements)
3
22
0
Order By: Relevance
“…The effects of physical exercise on depression‐like symptoms and diabetic factors have been monitored independently, but surprisingly, to the best of our knowledge, not concomitantly. For instance, treadmill exercise decreased glycated hemoglobin, hemoglobin A1C (HbA1c), and inflammation levels in T1DM rats (Kazemi, 2019), whereas it reduced depressive behavior and corrected the modification of dendritic spines in the brains of depressed rats (Zhuang et al., 2019). Tables 1 and 2 compile some of the recent studies that test the effect of physical exercise interventions on depression and T2DM in humans and animal models, respectively.…”
Section: Possible Intervention Management and Treatment Strategiesmentioning
confidence: 99%
“…The effects of physical exercise on depression‐like symptoms and diabetic factors have been monitored independently, but surprisingly, to the best of our knowledge, not concomitantly. For instance, treadmill exercise decreased glycated hemoglobin, hemoglobin A1C (HbA1c), and inflammation levels in T1DM rats (Kazemi, 2019), whereas it reduced depressive behavior and corrected the modification of dendritic spines in the brains of depressed rats (Zhuang et al., 2019). Tables 1 and 2 compile some of the recent studies that test the effect of physical exercise interventions on depression and T2DM in humans and animal models, respectively.…”
Section: Possible Intervention Management and Treatment Strategiesmentioning
confidence: 99%
“…Consistently, rodent models of depression trigger structural alterations of neurons [16] and decrease synaptic proteins level [31] in brain regions involved in mood regulation although variations in the severity and localization of these dysfunctions have been reported. For example, coherently with the amygdaloid centered model of stress [32] UCMS administered for periods ranging between 1 to 3 months elicits spine loss and dendritic arbor retraction in hippocampus and medial prefrontal cortex [12,33] but increases spines in amygdala and nucleus accumbens [6,34]. On the functional level, it has been suggested that reduction of mPFC synaptic density decreases cortical activity, prevents fear extinction to develop but, at the same time, is permissive for amygdala hyperactivation due to the diminished control of PFC projections on BLA excitatory neurons.…”
Section: Discussionmentioning
confidence: 98%
“…Accumulating evidence has shown that in the hippocampus, chronic stress may alter cellular functions and plasticity of neurons, and result in dendritic atrophy as well as inhibition of neurogenesis [ 23 ]. In particular, chronic stress can also induce dendritic atrophy and reduce the length of apical dendrites of pyramidal neurons in the CA1 and CA3 regions, which may reduce neuroplasticity [ 24 , 25 , 26 ]. Furthermore, since GABAergic interneurons of the hippocampus are important in the regulation of cellular and neural circuit function, their roles in the pathogenesis of MDD have been well documented [ 27 ].…”
Section: Discussionmentioning
confidence: 99%